Short-term consumption of alcohol (vodka) mixed with energy drink (AMED) attenuated alcohol-induced cerebral capillary disturbances and neuroinflammation in adult wild-type mice. (2nd November 2022) - Takechi, Ryusuke; Mamo, John; Das, Sukanya; Graneri, Liam; D'Alonzo, Zachary; Nesbit, Michael; Junaldi, Edwin; Lam, Virginie
ABSTRACT: Background: The ingestion of combinatory Alcohol Mixed with Energy Drink (AMED) beverages continues to increase markedly, particularly among young adults. Some studies suggest detrimental health effects related to the combination of alcohol with energy drink formulations; however, the consumption of AMED has not been investigated in context of the cerebral microvasculature or neuroinflammation. We hypothesized that cerebral capillary integrity and glial cells are particularly vulnerable to the combination of AMED. Methods: 12-week old wild-type C57BL/6J mice were orally gavaged with either vehicle (water), alcohol (vodka), an energy drink (Mother TM ), or a combination AMED, daily for five days. Thereafter, mice were sacrificed, blood alcohol concentrations were analysed and cryosections of brain specimens were subjected to confocal immunofluorescent analysis for measures of cerebral capillary integrity via immunoglobulin G (IgG), and markers of neuroinflammation, ionized-calcium-binding-adaptor-molecule 1 (Iba1) and Glial-Fibrillary-Acidic-Protein (GFAP). Proinflammatory cytokines, IL-2, IL-17A, IFN-ϒ, and anti-inflammatory cytokines, IL-4, IL-6 and IL-10, were also measured in serum. Results: Consistent with previous studies, cerebral capillary dysfunction and astroglial cell activation were markedly greater in the alcohol-only group (AO); however, the AO-induced effects were profoundly attenuated with the AMED combination. Mice maintained on AO and AMED interventions exhibited a moderate increase in microglial recruitment. There were no significant changes in pro-inflammatory nor anti-inflammatory cytokines in ED or AMED treated mice. Conclusion: This study suggests that paradoxically the acute detrimental effects of alcohol on cerebral capillary integrity and astrogliosis are counteracted with the co-provision of an ED, rich in caffeine and taurine and containing B-group vitamins.